Minimally Invasive Posterior Cervical Foraminotomy as an Alternative to Anterior Cervical Discectomy and Fusion for Unilateral Cervical Radiculopathy: A Systematic Review and Meta-analysis. Issue 24 (15th December 2019) - Sahai, Nikhil; Changoor, Stuart; Dunn, Conor J.; Sinha, Kumar; Hwang, Ki Soo; Faloon, Michael; Emami, Arash
Abstract : Study Design: Systematic review and meta-analysis. Objective: The aim of this study was to evaluate clinical outcomes, complications, and reoperations of minimally invasive posterior cervical foraminotomy (MI-PCF) for unilateral cervical radiculopathy without myelopathy, in comparison to anterior cervical decompression and fusion (ACDF). Summary of Background Data: ACDF is a standard treatment for cervical radiculopathy secondary to lateral disc herniation or foraminal stenosis. Recent studies have suggested MI-PCF to be an effective alternative to ACDF. However, concern for reoperation and whether similar improvements in clinical outcomes can be achieved has led to a debate in the literature. Methods: We comprehensively searched PubMed, CINAHL Plus, and SCOPUS utilizing terms related to MI-PCF. Two independent reviewers assessed potential studies and extracted data on clinical outcome scores (neck disability index [NDI], visual analog scale [VAS]-neck, and VAS-arm), reoperation proportion, and complications. Studies included were on noncentral cervical pathology, published in the last 10 years, had a sample size of >10 patients, and reported data on minimally invasive techniques for posterior cervical foraminotomy. Heterogeneity and publication bias analyses were performed. The pooled proportions of each outcome were compared to those of ACDF obtained from two previously published studies. Results: Fourteen studies were included with data of 1216 patients. The study population was 61.8% male, with a mean age of 51.57 years, and a mean follow-up of 30 months. MI-PCF resulted in a significantly greater improvement in VAS-arm scores compared to ACDF, and similar improvements in VAS-neck and NDI scores. Proportions of complications and reoperations were similar between the two cohorts. The most common complications were transient neuropraxia, wound-related, and durotomy. Conclusion: Our findings suggest that MI-PCF may be utilized as a safe and effective alternative to ACDF in patients with unilateral cervical radiculopathy without myelopathy, without concern for increased reoperations or complications. Level of Evidence: 3 Abstract : There is debate concerning the treatment of unilateral cervical radiculopathy. Minimally invasive posterior cervical foraminotomy (MI-PCF) results in improved clinical outcome scores, with similar reoperation and complication rates to anterior cervical decompression and fusion (ACDF). Therefore, MI-PCF can be considered a safe and effective alternative to ACDF in these patients.